Bond strength of different orthodontic brackets produced with different materials and fabrication methods - de Souza Araújo, Isaac Jordão; Matté Zanini, Maurício; Favarão, Jamille; Puppin Rontani, Regina Maria; Bortolazzo Correr, Américo; Coelho Sinhoreti, Mário Alexandre (Brazilian Dental Science, 2022)
Objective: The aim of this study was to evaluate the effects of material and processing methods on the bond strength of orthodontic brackets. Material and Methods: Five types of brackets were tested: Conventional metallic (CM), metallic sandblasted (SB), ceramic (C), polycarbonate (PC), and metallic fabricated by melting injection molding (MIM). Shear bond strength (SBS) was conducted to check bond strength of the brackets bonded to bovine teeth (n=10/group), and tensile bond strength (TBS) (20 brackets/group) to check bracket retention to bonding material (n=20/group). Both, SBS and TBS were conducted with 1mm/min crosshead speed in a universal testing machine. Bond strength was calculated in Megapascal (MPa) based on force (N) and bracket area (mm2). Data normality was verified, and One-way ANOVA was the statistical test with Tukey posthoc (a=0.05). Results: SB and MIM presented higher SBS compared to C, PC, and CM (p<0.05). SB and MIM also presented significantly higher TBS compared to CM and PC (p<0.05). However, MIM was not different of C for TBS. Conclusion: The type of material and method of fabrication are determinant factors that affect bond strength of orthodontic brackets and melting injection molding (MIM) is a remarkable technology to improve brackets retention during the orthodontic treatment. KEYWORDS Bond strength; Orthodontic brackets; Melting injection molding.